Short note:The fecundity and egg size of the freshwater crab(Isolapotamon bauense Ng,1987)from Sarawak, Borneo - Lirong, Yu Abit; Mohd. Zafri, Hassan; Kamil, Latif; Jongkar, Grinang; Abdulla, Al-Asif (2020)
The Island of Borneo harbors a high species richness of freshwater brachyurans, many of which are endemic in the region and their existence is threatened by an thropogenic activities. Our knowledge on the fundamental aspects which are required for species conservation assessment is currently limited. For instance, information on fecundity of most Bornean freshwater crabs is almost non-existent despite this being an important predictor of vulnerability to extinction. This paper describes the fecundity and egg size of the giant freshwater crab(Isolapotamon bauense Ng,1987)from Kuching Division in Sarawak, Borneo. The fecundity of the crab is between 26and 81 eggs, with the egg diameter ranging between 3.7–4.2 mm. The macrolecithal eggs are attached to the pleopods of the female abdominal brood pouch;they are bright orange and are comprised of two layers of membrane, with a thicker outer layer and a thinner inner layer,encapsulating the large embryonic yolk sac.